2016
DOI: 10.1190/tle35100850.1
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse full-waveform inversion as a reservoir-monitoring tool — A North Sea case study

Abstract: Full-waveform inversion (FWI) has become an enabling tool for 3D velocity-model building, especially in the shallow part of the seismic image that is well probed by diving waves. Given that FWI provides direct access to P-wave velocities, its application to time-lapse (4D) studies is of obvious interest. Can 4D FWI give fast access to small reservoir production-related velocity changes and compete with traditional 4D time-shift results based on fully processed and imaged reflection data? Also, what algorithmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…() and Hicks et al . () have already done investigations based on this model. They showed that full‐waveform inversion (FWI) is capable of recovering production‐related changes and local changes caused by waste injection with reasonable accuracy (although with lower resolution and amplitude than the true one).…”
Section: Synthetic Data Example Based On a Realistic Time‐lapse Modelmentioning
confidence: 99%
“…() and Hicks et al . () have already done investigations based on this model. They showed that full‐waveform inversion (FWI) is capable of recovering production‐related changes and local changes caused by waste injection with reasonable accuracy (although with lower resolution and amplitude than the true one).…”
Section: Synthetic Data Example Based On a Realistic Time‐lapse Modelmentioning
confidence: 99%
“…In differential or double-difference waveform inversion the baseline model is inverted first and then the monitor model is constructed based on double-difference misfit functional (Denli et al, 2009), which allows us to reduce artifacts due to imperfect baseline model inversion. Oghenekohwo et al 2015and Hicks et al (2016) proposed to exploit common information between the baseline and monitor data and models in joint inversion and common model inversion respectively. Common information makes inversion for reference model more robust.…”
Section: Cdwi Inversion Strategymentioning
confidence: 99%
“…; Hicks et al . ). In most of the strategies, the baseline survey is inverted first, and then the strategies differ in how the second inversion is performed.…”
Section: Introductionmentioning
confidence: 97%